La commission des valeurs mobilières du Québec - Guy, Paul (Assurances, 1987)
Briefly, the mission of the Quebec Securities Commission is to keep a watchful eye on the securities market and ensure it runs smoothly. We would like to thank the Commission's current President, Mr. Paul Guy, for having accepted our invitation to describe, in the following pages, the role and structure of the Commission, its relation with the persons under its surveillance, the services it offers and the current economic outlook.